The Administrative Skills Required for Basic School Principals as seen by the Teachers of These Schools in Irbid Governorate - Mashatlah, Hanan Ahmad (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the Administrative skills required for school principals as perceived by the teachers of those schools. The researcher used the descriptive survey approach, and the tool consisted in a questionnaire consisting of (56) items distributed into seven areas that were distributed to a random sample of (250) teachers from all basic schools In Irbid Governorate, and they represent (6%) of the study population of (4150)teacher. It showed the results of the study; The general management skills of basic school principals as perceived by teachers in Irbid governorate attain an overall average (4.15 out of 5), i.e. with a (large) level of application, and at the level of fields. The area of ​​self-skills got the highest average (4.36), then the field of time management with an average (4.27), both of them with (very large), the third of which is the area of ​​financial resources management with an average (4.14), and fourth is the area of ​​decision-making with an average (4.13), and the fifth is the area of ​​strategic planning with an average (4.12), sixth in the field of information technology with an average of (4.05), and finally in the field of community service with an average of (3.86), all of which have an application estimate of (large), and the results also showed that there are no statistically significant differences at the level of significance (α= 0.05) attributed to the two variables (sex, and experience), while statistically significant differences were found at (α=0.05) due to the effect of qualification and the differences came in favor of bachelor's holders. Based on the results, the researcher presented a set of recommendations and proposals to upgrade the administrative skills of principals of basic schools in the governorate of Irbid and the whole Kingdom of Jordan.
Keywords: Administrative Skills; Principals Basic Schools; Irbid Governorate